2023
DOI: 10.1038/s41564-023-01349-3
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-derived macrophages contain persistent latent HIV reservoirs

Abstract: The development of persistent cellular reservoirs of latent human immunodeficiency virus (HIV) is a critical obstacle to viral eradication since viral rebound takes place once anti-retroviral therapy (ART) is interrupted. Previous studies show that HIV persists in myeloid cells (monocytes and macrophages) in blood and tissues in virologically suppressed people with HIV (vsPWH). However, how myeloid cells contribute to the size of the HIV reservoir and what impact they have on rebound after treatment interrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…Recent work in nonhuman primates (NHPs) has shown a relatively rapid turnover of macrophages [24], raising questions about their longevity as a significant HIV latency reservoir. Strikingly, monocyte-derived macrophages from PWH appear to harbor latent HIV for years despite successful cART [25 ▪ ]. Considering the short lifespan of monocytes, researchers speculate that progenitors are infected with HIV or that HIV seeds monocytes in compartmentalized tissues.…”
Section: The Importance Of Latent Hiv Reservoir For the Cure Of Hivmentioning
confidence: 99%
“…Recent work in nonhuman primates (NHPs) has shown a relatively rapid turnover of macrophages [24], raising questions about their longevity as a significant HIV latency reservoir. Strikingly, monocyte-derived macrophages from PWH appear to harbor latent HIV for years despite successful cART [25 ▪ ]. Considering the short lifespan of monocytes, researchers speculate that progenitors are infected with HIV or that HIV seeds monocytes in compartmentalized tissues.…”
Section: The Importance Of Latent Hiv Reservoir For the Cure Of Hivmentioning
confidence: 99%
“…For example, while lymphoid-resident CD4+ T cells are the well-known cell reservoir for HIV, new studies using single-cell RNA sequencing found that individual CD4+ T cells exhibit distinct gene expression; findings suggest some were under immune selection and another subset actively facilitated HIV replication (Sun et al 2023). Newer studies have found additional HIV reservoirs in monocyte-derived macrophages (Veenhuis et al 2023) or cerebrospinal fluid–resident CD4+ T cells (Kincer et al 2023). Epstein-Barr virus (EBV) can also establish a lifelong infection, can cause various malignancies, and may be associated with autoimmune disorders such as Sjögren’s disease, lupus, multiple sclerosis, and rheumatoid arthritis (Houen and Trier 2021), classically targeting epithelial and B cells, but it has also been shown to infect and persist in T cells and natural killer cells (Fournier et al 2020).…”
Section: Linking the Biogeography Of Host Cell Types And Niche-specif...mentioning
confidence: 99%
“…Finally, it should be noted that our current understanding of the role of CARD8-driven pyroptosis in HIV infection is mostly based on T-cell reservoirs. In the last few years, a growing body of work has provided evidence that macrophages are an important and often underestimated contributor to the reservoir [3]. In contrast to CD4 + T cells, which do not produce IL-18 and IL-1β upon CARD8 activation, macrophages are able to generate a robust proinflammatory response upon CARD8 activation [60 ▪▪ ], with the potential to fuel chronic inflammation locally and perhaps systemically.…”
Section: The Card8 Inflammasome and Pyroptosismentioning
confidence: 99%
“…Although the introduction of effective antiretroviral therapy (ART) has transformed HIV into a chronic disease [1], most people with HIV (PWH) require lifelong treatment to maintain virological suppression. This is due to the persistence of a small but heterogeneous reservoir of latently infected cells (mainly resting CD4 þ T cells and myeloid cells), which are responsible for viral rebound when ART is stopped [2,3].…”
Section: Introductionmentioning
confidence: 99%